Pemberian Abolisi terhadap Terpidana Korupsi: Analisis Konvensi Ketatanegaraan dan Siyasah Iddariyah - Lia Rahmawati; Retanisa Rizqi (Institut Agama Islam Negeri Kerinci, 2025)
The granting of abolition constitutes a constitutional prerogative of the President as stipulated in the 1945 Constitution of the Republic of Indonesia; however, its application to perpetrators of corruption raises serious debates concerning legal morality and anti-corruption efforts. This article aims to analyze the President’s authority to grant abolition to corruption offenders from the perspectives of constitutional law and siyāsah iddariyah. This study employs a qualitative library research design using a normative-analytical approach through the examination of statutory regulations, court decisions, and relevant legal literature. The findings indicate that although the authority to grant abolition has a constitutional basis, its application to corruption cases potentially contradicts the principles of substantive justice, the spirit of combating corruption, and the protection of public interest. From the perspective of siyāsah iddariyah, the exercise of governmental authority is constrained by the principles of trust (amānah), justice, and the safeguarding of the public good; therefore, policies on abolition must be oriented toward the preservation of maqāṣid al-sharī‘ah, particularly the protection of state assets and public trust. Accordingly, the granting of abolition to corruption offenders should be applied in a strict and proportional manner and oriented toward the public interest to prevent abuse of power and the erosion of legal morality.